2007
DOI: 10.1128/aac.00526-07
|View full text |Cite
|
Sign up to set email alerts
|

Steady-State Pharmacokinetic and Safety Profiles of Voriconazole and Ritonavir in Healthy Male Subjects

Abstract: Since there is a likelihood of coadministration of voriconazole and ritonavir, two studies were conducted to evaluate the potential of drug interaction. Study A was a randomized, placebo-controlled, two-period, parallelgroup trial (n ‫؍‬ 34). Study B had the same design without the placebo group (n ‫؍‬ 17). In period 1, subjects received 200 mg voriconazole or placebo twice daily (BID) for 3 days (400 mg BID on day 1). In period 2, following a 7-day washout, subjects received ritonavir alone at 400 mg BID (stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
36
0
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 30 publications
1
36
0
3
Order By: Relevance
“…Consequently, these data could not be used to develop a population pharmacokinetic model. Nevertheless, phase I studies suggest that there is low intra-individual variation in plasma concentrations relative to inter-individual variability (22,29,30), thus allowing the mean plasma concentration per patient (C avg ) to be used as a measure of drug exposure.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, these data could not be used to develop a population pharmacokinetic model. Nevertheless, phase I studies suggest that there is low intra-individual variation in plasma concentrations relative to inter-individual variability (22,29,30), thus allowing the mean plasma concentration per patient (C avg ) to be used as a measure of drug exposure.…”
Section: Methodsmentioning
confidence: 99%
“…1 (see text). AUC area under the plasma concentration-time curve is frequently prescribed, and interactions due to ritonavir (21)(22)(23) and telaprevir, which are strong inhibitors. These predictions showed that the interactions with colchicine result in AUC ratios that are never >3.5, whereas ritonavir and telaprevir were confirmed as strong inhibitors with an IR of 0.99 and 0.97, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Ritonavir, which is not only a CYP3A4 inhibitor, was nevertheless included because its properties have been well characterized. Ritonavir is also an inhibitor of CYP2D6 and P-glycoprotein and an inducer of CYP2C9 and CYP2C19 (21)(22)(23). To estimate and validate the IR of ritonavir, we selected interaction studies for which CYP3A4 inhibition was thought to be the major mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Ritonavir is a potent CYP3A, CYP2D6 and P-glycoprotein inhibitor [16][17][18]. It has been described to induce CYP1A2, CYP2B6, CYP2C9 and CYP2C19 [19,20]. Difficult dosing regimens, the development of resistance and adverse effects have restricted the use of ritonavir as an independent part of HIV treatment [21].…”
mentioning
confidence: 99%